Verbos polissêmicos: propriedades semânticas e processos metafóricos - Maria Aparecida Damasceno Netto de Matos (2006)
This dissertation explores the way that some polyseman verbs behave in Brazilian Portuguese, associating them to the possible thematic role assignments. The research is based on CANÇADOs Thematic Role Theory (2003, 2005a). In this study, the verbs are classified in three different groups, according to the semantic properties trigger, affected, state, and control . In addition, we used LAKOFF & JOHNSON (1980, 2002) cognitive semantic proposal. Initially, we explore the explanation of the polysemic process, suggested by LAKOFF & JOHNSON. Secondly, we draw up the relationship between the thematic network of the verbs and cognitive process of the polysemic creation.